Penerapan Administrasi Manajemen Perbankan pada Bank Tabungan Negara Kantor Cabang Mataram - Subagyo, Areebah; Monica Chandra Wijayanti; Ni Komang Santi Widyaswari A. N. (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
This study examines the implementation of banking management administration at PT Bank Tabungan Negara (persero) Tbk, Mataram Branch Office. The aim is to evaluate the effectiveness of administrative processes and identify challenges faced in performing administrative tasks. Research methods include direct observation, interviews with bank staff, and document analysis. The findings indicate that the administrative processes at PT Bank Tabungan Negara (persero) Tbk, Mataram Branch Office function well, despite some technical challenges such as delays in archiving and data entry errors. These issues can be addressed through continuous training for employees and enhanced inter-departmental coordination. The author also emphasizes the importance of upgrading technological infrastructure to support work efficiency. Other recommendations include improving the information management system and developing orientation programs for new employees. The internship at PT Bank Tabungan Negara (Persero) Tbk Mataram Branch Office provides real work experience, enhances both technical and soft skills, and helps students adapt to workplace culture while building professional networks in the banking industry. Overall, this study provides insights into the importance of effective administration in banking operations and offers practical solutions to enhance administrative performance at PT Bank Tabungan Negara (persero) Tbk, Mataram Branch Office.